Gac fruit (Momordica cochinchinensis Spreng): From nutritional value to food processing technology - Siti Alyani, Mat; El Enshasy, Hesham Ali; Nadirah, Abd Rahim; Chong, Xin Nih; Vadiveloo, Sajetra Devi; Harisun, Ya’akob; Dailin, Daniel Joe; Chew, Dennis Sing Teong; Nor Hasmaliana, Abdul Manas (Elsevier Ltd, 2024)
Gac (Momordica cochinchinensis Spreng.) fruit, which originates from Southeast Asia, is widely recognized for its rich nutritional profile and its traditional medicinal applications. The fruit's commercialization in functional food products is driven by its potent antioxidant, antibacterial, anti-inflammatory, anticancer, neurotropic, and immunomodulatory properties. Additionally, gac fruit is not widely consumed commercially as food, making it less competitive in the food market. However, processing can compromise these benefits due to the degradation of active compounds under harsh conditions. This review explores the nutrient composition and functional properties of gac fruit, evaluates common processing techniques, and highlights strategies for nutrient preservation during processing. Emphasizing the importance of continued research, innovative processing, and sustainable practices, the article underscores the potential of gac fruit to significantly impact global health and wellness. Effective preservation strategies are crucial not only for enhancing consumer health but also for bolstering the economic viability of gac fruit in the global market.